Islamic Philanthropy in the Digital Era: Intercultural Communication Strategies for Effective ZISWAF Campaigns - Setawan, Donny; Murodi; Arief Subhan; Nurliana; Trisia Megawati; Abdul Khakim (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
The main issue in the Zakat, Infaq, Shadaqah, and Wakaf (ZISWAF) campaign in the digital era is how to effectively manage communication in a multicultural context. The objective of this research is to identify communication strategies that can inclusively reach multicultural communities. The core statement of this research is that effective intercultural communication is crucial for increasing participation in the ZISWAF campaign. The theory used is John Fiske's semiotic theory, which explains how messages are encoded and decoded by different audiences. The analysis shows that the use of cultural symbols and technology-based approaches can enhance the effectiveness of the ZISWAF campaign. The conclusion of this research is that culturally sensitive communication strategies, supported by digital technology, can increase community engagement in ZISWAF management and strengthen the impact of Islamic philanthropy.